Cinematic realism : Lukács, Kracauer and theories of the filmic real - Aitken, Ian (Edinburgh University Press, 2020)
Explores classical and contemporary theories of cinematic realism to assess their overall key concepts and intellectual configurations. Explores classical theories of cinematic realism more deeply through an analysis of Lukacs/Bergson/time and Kracauer/Husserl/Space. Offers some conclusions on what the central key concepts and intellectual configuration of cinematic realism are; and on what consequences flow from this. The issue of cinematic realism is important because the issue of realism, of the relationship between representation and reality, is important. If some forms of representation are closer to reality - however defined - than others, then this may also be the case with forms of filmic representation. In this book, Ian Aitken links the issue of cinematic realism to important questions concerning human experience, analysing the close similarity between the film image and visual perception, and how different theories of realism have sought to uncover the way film's relation to reality can be understood. Focusing on the writings of Georg Lukacs and Siegfried Kracauer, Cinematic Realism is a comprehensive exploration of cinematic realist theory.